Evaluation of Dietary Phytogenics on Growth Performance and Carcass Characteristics of Pigs During the Growing-Finishing Phase - J. Soto; M. D. Tokach; S. S. Dritz; J. C. Woodworth; J. M. DeRouchey; R. D. Goodband (Kansas Agricultural Experiment Station Research Reports, 2017)
A total of 317 pigs (DNA 600 × 241, initially 108.6 lb) were used in a 87-d trial to determine the effects of two essential oil mixtures tested individually and in combination on growth performance and carcass characteristics of growing-finishing pigs from 108 to 285 lb. Pens of 9 or 10 mixed-gender pigs were allotted by BW and randomly assigned to 1 of 4 dietary treatments with 8 replications per treatment. Pigs were fed a nutritional program with 4 dietary phases with the same treatments fed in all 4 phases. Experimental treatments included a control diet with no feed additives or the control with 0.02% essential oil mixture 1 (EOM 1) containing caraway, garlic, thyme, and cinnamon; 0.013% essential oil mixture 2 (EOM 2) containing oregano, citrus, and anise; and the combination of 0.02% EOM 1 and 0.013% EOM 2 (EOM 1+2). At d 87, pigs were transported to a packing plant for processing and carcass data collection. There was no evidence for treatment differences for overall ADG, ADFI, or F/G. Similarly, there was no evidence for treatment differences in HCW, carcass yield, backfat, loin depth or percentage lean. In summary, the inclusion of these phytogenic feed additives did not influence growth or carcass performance.
Keywords: growing-finishing pigs; feed additives; phytogenics; essential oils